1990
DOI: 10.2307/1937592
|View full text |Cite
|
Sign up to set email alerts
|

A Colonization Strategy in Field Voles (Microtus Agrestis): Reproductive Traits and Body Size

Abstract: Populations of the field vole (Microtus agrestis) in the Stockholm Archipelago in the Baltic (southern Sweden) are highly dynamic, with frequent extinctions and recolonizations of islands. In order to investigate the demography of such a successful island colonizer, I studied reproductive traits in two breeding colonies of Swedish field voles, one mainland and one from the archipelago, which I kept in a laboratory for 3 yr. Insular voles, as compared to mainland voles, were characterized by a larger adult body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 51 publications
2
36
0
1
Order By: Relevance
“…Local extinctions and recolonizations from neighbouring islands are frequent in insular populations of field voles [11 -13], and breeding experiments have demonstrated that insular voles have evolved different life-history characteristics (i.e. produce more and larger young that grow faster, and make a larger reproductive effort) than mainland voles [10]. The larger body size with increasing distance from the mainland and increasing inter-island fragmentation may thus represent a correlated response to selection for traits that enhance reproductive performance in dynamic metapopulation systems [11,13,42,43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Local extinctions and recolonizations from neighbouring islands are frequent in insular populations of field voles [11 -13], and breeding experiments have demonstrated that insular voles have evolved different life-history characteristics (i.e. produce more and larger young that grow faster, and make a larger reproductive effort) than mainland voles [10]. The larger body size with increasing distance from the mainland and increasing inter-island fragmentation may thus represent a correlated response to selection for traits that enhance reproductive performance in dynamic metapopulation systems [11,13,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…(b) Laboratory common garden experiment We used wild-caught voles from the mainland site U and from the insular localities A þ R þ H (figure 1) as breeding nuclei for one mainland and one insular colony kept in the laboratory for a period of three years. Detailed information on the breeding schedule and housing conditions are given elsewhere [10]. A total of 463 litters were produced by 100 females and 101 males.…”
Section: (A) Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual dimorphism in morphological characters as well as in foraging behaviour and diets has been demonstrated in birds (Selander, 1966(Selander, , 1972 and mammals (Erlinge, 1981;Moors, 1980). For species with indeterminate growth such a difference is harder to imagine since the sexes will be overlapping in adult body size.…”
mentioning
confidence: 99%
“…Segundo, o tamanho do corpo pode diferir por modificação genética local (possivelmente por adaptação) ou mesmo devido a um efeito fenotípico direto da disponibilidade de alimento nas taxas de crescimento . Características ecológicas como diversidade de espécies, competição interespecífica e dimensões de nicho variam geograficamente e podem afetar a disponibilidade de alimento em populações diferentes (BERRY et al, 1987;EBENHARD, 1990).…”
Section: Introductionunclassified